Prognostic Value of Hepatocyte Growth Factor, Syndecan-1, and Osteopontin in Multiple Myeloma and Monoclonal Gammopathy of Undetermined Significance. (26th April 2012) - Minarik, Jiri; Pika, Tomas; Bacovsky, Jaroslav; Petrova, Pavla; Langova, Katerina; Scudla, Vlastimil
Abstract : Our aim was to compare serum levels of selected biological parameters in different phases of multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS) to determine their diagnostic and prognostic potential. A cohort of 234 individuals was assessed for serum levels of hepatocyte growth factor (HGF), syndecan-1/CD138 (SYN), and osteopontin (OPN). The patients with MM (N = 156 ) were divided into 3 groups: at the time of diagnosis (N = 45 ), in relapse/progression (N = 56 ), and in remission (N = 50 ). The analysis revealed significant differences of all three parameters in comparison of active and remission phase MM. Moreover, the parameters in active myeloma were significantly higher than in MGUS. Within the comparison of active disease (newly diagnosed and relapsing), there was no significant difference. Similar results were in remission phase MM and MGUS. There was no relationship of pretreatment levels of the parameters to therapeutic response. We conclude that serum levels of HGF, OPN, and SYN correspond to the activity of MM and might become useful in differentiation of MGUS, asymptomatic MM, and overt/symptomatic form of MM. The levels of all three parameters behave accordingly with MM activity. Pretreatment measurement without the assessment of their kinetics, however, has no relationship to therapeutic response.